Alkyl-substituted spiropyrans: electronic effects, model compounds and synthesis of aliphatic main-chain copolymers. Issue 35 (10th August 2017) - Schmidt, Simon B.; Kempe, Fabian; Brügner, Oliver; Walter, Michael; Sommer, Michael
Abstract : This work reports on the isomerisation behaviour of alkylated spiropyrans and aliphatic main chain spiropyran copolymers. Abstract : The isomerisation behaviour of spiropyrans (SP) depends considerably on their substituents. This work investigates the synthesis, isomerisation behaviour and polymer chemistry of alkylated spiropyrans. While several Kumada- and Suzuki-based protocols failed to alkylate dibromo-spiropyran, classical 9-BBN chemistry is shown to proceed with high yield suitable also for polycondensation. Alkyl substituents strongly influence the acid-induced SP-merocyanine (MC)-protonated MC (MCH + ) equilibrium and render the MCH + form most stable. In agreement with measured isomerisation rates, density functional theory calculations corroborate the enhanced stabilisation of ethyl-substituted MCH + as compared to phenyl-substituted MCH + . Aliphatic main chain spiropyran copolymers are synthesised from in situ generated bis-9-BBN monomers and dibromo-spiropyrans. The empirical optimisation of stoichiometry yields a molecular weight M w of ∼15 kg mol −1 after purification. This approach to alkylated spiropyrans opens new opportunities to fine-tune the isomerisation behaviour of small molecules and polymeric SP derivatives for potential use as sensors and smart materials.